In Vitro Activities of Nisin and Nisin Derivatives Alone and In Combination with Antibiotics against Staphylococcus Biofilms - Field, Des; O’ Connor, Rory; Cotter, Paul D.; Ross, R. Paul; Hill, Colin (Frontiers in Microbiology, 2016)
The development and spread of pathogenic bacteria that are resistant to the existing catalogue of antibiotics is a major public health threat. Biofilms are complex, sessile communities of bacteria embedded in an organic polymer matrix which serve to further enhance antimicrobial resistance. Consequently, novel compounds and innovative methods are urgently required to arrest the proliferation of drug-resistant infections in both nosocomial and community environments. Accordingly, it has been suggested that antimicrobial peptides could be used as novel natural inhibitors that can be used in formulations with synergistically-acting antibiotics. Nisin is a member of the lantibiotic family of antimicrobial peptides that exhibit potent antibacterial activity against many Gram-positive bacteria. Recently we have used bioengineering strategies to enhance the activity of nisin against several high profile targets, including multi-drug resistant clinical pathogens such as methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), staphylococci and streptococci associated with bovine mastitis. We have also identified nisin derivatives with an enhanced ability to impair biofilm formation and to reduce the density of established biofilms of methicillin resistant Staphylococcus pseudintermedius (MRSP). The present study was aimed at evaluating the potential of nisin and nisin derivatives to increase the efficacy of conventional antibiotics and to assess the possibility of killing and/or eradicating biofilm-associated cells of a variety of staphylococcal targets. Growth curve-based comparisons established that combinations of derivatives nisin V + penicillin or nisin I4V + chloramphenicol had an enhanced inhibitory effect against S. aureus SA113 and S. pseudintermedius DSM21284 respectively compared to the equivalent nisin A + antibiotic combinations or when each antimicrobial was administered alone. Furthermore, the metabolic activity of established biofilms treated with nisin V + chloramphenicol and nisin I4V + chloramphenicol combinations revealed a significant decrease in S. aureus SA113 and S. pseudintermedius DSM21284 biofilm viability respectively compared to the nisin A + antibiotic combinations as determined by the rapid colorimetric XTT assay. The results indicate that the activities of the nisin derivative and antibiotic combinations represent a significant improvement over that of the wild-type nisin and antibiotic combination and merit further investigation with a view to their use as anti-biofilm agents.